UHPLC-PDA Assay for Simultaneous Determination of Vitamin D3 and Menaquinone-7 in Pharmaceutical Solid Dosage Formulation. (21st August 2017) - Jehangir, Muhammad; Ahmed, Mahmood; Imtiaz Shafiq, Muhammad; Samad, Abdul; Iftikhar-ul-Haq,
Abstract : A newly developed method based on ultrahigh performance liquid chromatography (UHPLC) was optimized for the simultaneous determination of vitamin D3 and menaquinone-7 (MK-7) in tablet formulation in the present study. UHPLC separation of vitamin D3 and MK-7 was performed with ACE Excel 2 C18-PFP column (2 μ m, 2.1 × 100 mm) at 0.6 mL min −1 flow rate, whereas the mobile phase consisted of methanol/water (19 : 1, v/v, phase A) and isopropyl alcohol (99.9%, phase B) containing 0.5% triethylamine. Isocratic separation of both the analytes was performed at 40°C by pumping the mobile phases A and B in the ratio of 50 : 50 (v/v, pH, 6.0). Both analytes were detected at a wavelength of 265 nm and the injection volume was 1.0 μ L. The overall runtime per sample was 4.5 min with retention time of 1.26 and 3.64 min for vitamin D3 and MK-7, respectively. The calibration curve was linear from 5.0 to 100 μ g mL −1 for vitamin D3 and MK-7 with a coefficient of determination (R 2 ) ≥ 0.9981, while repeatability and reproducibility (expressed as relative standard deviation) were lower than 1.46 and 2.21%, respectively. The proposed HPLC method was demonstrated to be simple and rapid for the determination of vitamin D3 and MK-7 in tablets.